Recent Advances in Biomarkers of Systemic Sclerosis-Associated Interstitial Lung Disease: Clinical Relevance and Therapeutic Perspectives - Rasha-Ioana Rămoiu-Shehada; Anca Emanuela Mușetescu; Lucian-Mihai Florescu; Alesandra Florescu; Paulina-Lucia Ciurea (Life, 2026)
Systemic sclerosis-associated interstitial lung disease (SSc-ILD) is the leading cause of mortality in patients with systemic sclerosis and a major clinical challenge due to its heterogeneous presentation and variable disease course. Reliable biomarkers may improve disease assessment, risk stratification, and therapeutic decision-making. This narrative review summarizes current evidence on established and emerging serum and molecular biomarkers in SSc-ILD and their potential clinical applications. Recent advances have shifted the focus from single-marker assessment toward integrated biomarker profiling, reflecting the complex pathogenesis of pulmonary fibrosis. KL-6 and surfactant protein D (SP-D) have been associated with pulmonary involvement and radiographic features of SSc-ILD. Inflammatory mediators, including interleukin-6 (IL-6), and autoantibodies such as anti-topoisomerase I (anti-Scl-70) have been associated with disease severity and an increased risk of pulmonary progression. Emerging biomarkers related to epithelial injury, extracellular matrix remodelling, and vascular dysfunction may provide additional insights into the biological mechanisms underlying SSc-ILD. Current evidence highlights the potential of circulating and molecular biomarkers to refine risk stratification and prognostic assessment in SSc-ILD. Prospective validation and methodological standardization remain necessary to determine their clinical utility and potential integration into personalized disease management.